Entrelaçamento entre Filosofia e Literatura: a obra de Kafka como via de acesso à filosofia de Nietzsche - SANTOS, Jamys Alexandre Ferreira (2018)
The present study is based on the relationship between philosophy and literature with Friedrich Nietzsche e Franz Kafka as the main authors studied. The central question of this study is how to comprehend some of Nietzsche’s philosophy in Kafka’s literary pieces? In this way, the goal is to analyze a potential reading of the concepts “will of power” and “nihilism” mainly in Para além do bem e do mal, Genealogia da moral, A vontade de poder and in Fragmentos Póstumos 1885-1887 by Nietzsche, and in Diários, in Carta ao pai and in the narrative A construção by Kafka taking into consideration the philosophical opening that the Czech enables. The text’s proposal develops in four moments: (1) point some of the aspects of Western thinking that affirm often conflicting relationship between literature and philosophy; (2) characterizing Nietzsche’s philosophy with the “will of power” and “nihilism” concepts as main points of the books considered as “mature” written by this author; (3) presenting Kafka’s pieces Diários and Carta ao pai as an alternative to “overcome ‘nihilism’” with the main starting point being the relationship between “will of power” and art characterized by a determined period in Nietzche’s philosophy as “active nihilism”; (4) and finally identifying Nietzche’s conception of nihilism and its types, as the philosopher proposes, in A construção by Kafka. Thus, the text primes at developing not just a descriptive analysis through bibliographic research focusing on the cited manuscripts, but also searching fundaments to arguments made by some commentators of both authors in specific points.